2018
DOI: 10.17219/acem/66354
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high intensity physical exercise and hypoxia on glycemia, angiogenic biomarkers and cardiorespiratory function in patients with type 1 diabetes

Abstract: Our study demonstrated that hypoxia combined with exercise reduces glycemia and may induce significant benefits in the prevention of diabetes cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…When drawing conclusions and making comparisons from some of the differences found in the literature regarding these effects, it must be considered that the regimen and the degree of hypoxia will lead to variation in the results ( Debevec and Millet, 1985 ); however, most of these studies tend to agree in showing that under hypoxia, glucose regulation is improved in both rats and humans ( Sawhney et al, 1986 ; Larsen et al, 1997 ; Woolcott et al, 2015 ; Sacramento et al, 2016 ). Moreover, this glucose improvement under different regimens of hypoxia would take some time and reach a plateau in the long term, resulting in rather normal value as observed in human studies ( Woolcott et al, 2015 ; Żebrowska et al, 2018 ) and in rats ( Chen et al, 2016 ). Therefore, the improved glucose regulation in rats under long-term CIH in this study supports the contribution of hypoxia to these phenomena and, to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 91%
“…When drawing conclusions and making comparisons from some of the differences found in the literature regarding these effects, it must be considered that the regimen and the degree of hypoxia will lead to variation in the results ( Debevec and Millet, 1985 ); however, most of these studies tend to agree in showing that under hypoxia, glucose regulation is improved in both rats and humans ( Sawhney et al, 1986 ; Larsen et al, 1997 ; Woolcott et al, 2015 ; Sacramento et al, 2016 ). Moreover, this glucose improvement under different regimens of hypoxia would take some time and reach a plateau in the long term, resulting in rather normal value as observed in human studies ( Woolcott et al, 2015 ; Żebrowska et al, 2018 ) and in rats ( Chen et al, 2016 ). Therefore, the improved glucose regulation in rats under long-term CIH in this study supports the contribution of hypoxia to these phenomena and, to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 91%
“…Duennwald et al [28] demonstrated that T1D individuals exposed to intermittent hypoxia (FiO₂ = 13.0 %) (5 × 6 min each day over 1-3 weeks) had improved ventilatory reflexes to Hx. The study by Zebrowska et al [29] showed that shorttime hypoxia (FiO₂ = 15.1 %) combined with graded exercise allowed more effective glycaemia control in T1D patients when compared with the exercise in normoxia. Submaximal exercise with hypoxia (FiO₂ = 14.0 %) may induce up-regulation of serum pro-angiogenic regulators compared to normoxia in T2D [23].…”
Section: Effects Of Hypoxia During Continuous and Intermittent Exercimentioning
confidence: 99%
“…Многие авторы допускают, что эффективным способом увеличения выживаемости человека в усло виях острой гипоксической гипоксии является ограничение физической активности, что лимитирует расход доступного для дыхания кислорода и субстратов биологического окисления [18,19,23]. При этом снижение метаболизма также может быть достигнуто за счет применения фармакологических веществ из класса антигипоксантов.…”
Section: Keywtrbunclassified